Comparison between Opioid and Non-Opioid Analgesia for Postoperative Pain in Obstetric Patients: 2437 - Qassim, Marwa A.; AlTaei, Alaa A (Journal of the Faculty of Medicine Baghdad, 2025)
Background: preventive analgesia using opioids has been the cornerstone in relieving postoperative pain. However, it carries undesirable side effect. The recent approach is to use other modalities instead. A lot of studies and researches have been done to evaluate ketorolac and Nefopam efficacy, duration of  pain relief and their side effects.Objectives: prospective study to evaluate the efficacy and duration action of ketorolac 30mg and nefopam 20mg in relieving postoperative pain in comparison to Pethidine 50mg in obstetric patients after cesarean section under general anesthesia.Methods: 120 patients included in this study. They were randomly divided in 3 groups. All received one of the 3 drugs involved in the study. Postoperative pain was assessed using Verbal rating scale-4 up to six hours after arrival to PACU. Patients received rescue drugs when they had moderate pain.Results: Ketorolac had showed results parallel to those of Pethidine with lesser adverse effects. Nefopam, on the other hand, was statistically significantly less efficient in relieving postoperative pain in comparison with Pethidine.Conclusion: single dose ketorolac can be used alone in the management of postoperative pain with similar efficacy to Pethidine and less nausea and vomiting. Nefopam is not as effective as Pethidine and it is not prudent to use it as a sole analgesic drug.